Streaming Unauthorised Copyrighted Content: Copyright Liability of Streaming Platforms and Streaming Box Distributors. A Comparative EU-US-SA Perspective - Pinkepank, Felix (Department of Commercial Law, 2019)
This thesis examines the liability for copyright infringement of streaming platforms and streaming box distributors in the EU, U.S. and in South Africa. As there have been no reported cases in South Africa in which copyright holders have instituted legal proceedings concerning copyright infringement against streaming platforms or streaming box distributors, this thesis analyses and compares the legal context in the EU and the U.S., in order to develop an appropriate approach for lawmakers and courts in South Africa regarding this issue. It concludes that the approach of the European Court of Justice with regard to the communication to the public right leads to legal uncertainty and should not be followed. Instead, it is suggested that South Africa implements into its Copyright Act of 1978 parts of the U.S. approach in terms of secondary liability. Furthermore, the lawmaker should revise the safe harbour provisions in the Electronic Communications and Transactions Act of 2002.